Analisis Ekspresi Klon Gen CVPD dalam Sel Escherichia Coli - Sri Mahayani, A.A. Putu (AGROKNOW, 2013)
Abstract. The effort to control CVPD was done, but it did not fulfil the expectation properly. One of the new approach to control the CVPD plant diseases were genetics approach expedient i.e. by isolating and resistant gene cloning or resistant against CVPD.Â Jeruk kingkit was far family of citrus plant which was resistant to CVPD. One of genetics transformation technique by Agrobacterium vector , have been isolated and cloned from DNA fragments successfully that were contain genes for resistance against CVPD disease (CVPDr gene) from Triphasia trifolia (Jeruk kingkit). Those DNA fragments were cloned in plasmid of pUC18 vector and were cared in the Escherichia coli JM109 cell, so that this research aims to detect CVPDr gene expression in the Escherichia coli JM109 cell, to compare CVPDr gene expression in the Escherichia coli JM109 cell with proteins which were isolated from T. trifolia and Siamese citrus.The bacteria were cultivated at liquid LB medium by adding agarose gel 1.5 g that contain ampicillin 100 ppm, and those bacteria were cultured at agarose gel LB medium that contain ampicillin 100 ppm. Colonies of growth bacterium were taken to be isolated their plasmids with the DNA agarose gel electrophoresis 1%. Obtainable DNA were cut by restriction enzymes endonuclease EcoRI and BamHI. Bacteria proteins were compared with the citrus plan proteins. Protein molecules which were yield from CVPDr gene cloning in the Escherichia coli JM109more or less 17 kDa its large. The similar large molecules exist at the sample proteins which were isolated from T. trifolia (Jeruk kingkit) .Kata kunci: Bakteri Escherichia coli JM109, CVPD, Jeruk kingkit., T. trifolia.